2014
DOI: 10.1016/j.futures.2014.01.013
|View full text |Cite
|
Sign up to set email alerts
|

The impact of national traditions and cultures on national foresight processes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…In all these studies, the focus is on the individual and to a lesser extent on communities and social contexts. Analysis of future attitudes in terms of national identities and shared narratives about the past is found in [19,51,52]. The focus here is on entire nations or a racial identities.…”
Section: Analysis: Interpreting Our Results Within Common Narratives mentioning
confidence: 99%
See 2 more Smart Citations
“…In all these studies, the focus is on the individual and to a lesser extent on communities and social contexts. Analysis of future attitudes in terms of national identities and shared narratives about the past is found in [19,51,52]. The focus here is on entire nations or a racial identities.…”
Section: Analysis: Interpreting Our Results Within Common Narratives mentioning
confidence: 99%
“…Most of this work has been carried out within English-speaking countries and is particularly suitable to the Australia setting [19,73,74]. It tends to see individual preferences towards economic management, government style, environmental protection, crime control and moral stands as highly clustered and closely related to ideological stances.…”
Section: Analysis: Interpreting Our Results Within Common Narratives mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the innovation systems literature emphasises that innovation systems and sectors cannot always be analysed independent of their national or territorial contexts [38], [49]. This is mirrored in the foresight literature, which has shown that national cultures and traditions are determinants of perceptions of the future and of how decision making takes place [2], [66]. Although foresight projects eventually want to derive a result that is aggregated across several countries, we must design the foresight process so that differences in national contexts can be examined or so that important details are not blurred by averaging across national or regional contexts.…”
Section: Discussionmentioning
confidence: 99%
“…But there is still a chance that a number of inconsistencies between the narrative and numerical simulation models will occur. Some authors believe that achieving consistency between the narrative and numerical outputs is "…one of the weakest links" [99]. Along similar lines, Kosow has pointed out that, "….Overall, transformation rarely allows a perfect fit between the driving forces described by the storylines and those needed as input parameters by the models" [35].…”
Section: Pitfall: Missing the Connection Between The Narrative And Numentioning
confidence: 99%